Evaluation of Radiosterilized Glyercerolated Amniotic Membranes as a Substrate for Cultured Human Epithelial Cells. (2nd January 2020) - Paggiaro, André O.; Mathor, Monica B; Teodoro, Walcy R.; Isaac, Cesár; Capelozzi, Vera L.; Gemperli, Rolf
ABSTRACT: Human amniotic membrane (HAM) is a biomaterial with biological properties beneficial to tissue repair, serving as a substrate for cell cultivation. Irradiation is used for tissue sterilization, but can damage the HAM structure. The objective of this paper was to construct a skin substitute, composed of human keratinocytes cultured on glycerolated HAMs, and to evaluate the influence radiation on subsequent cell culture growth. Four batches of HAMs were glycerolated, and half of them were radio-sterilzed with 25 kGy. Non-irradiated glycerolated HAM (ni-HAM) and irradiated glycerolated HAM (i-HAM) samples were then de-epithelized and analyzed using optical microscopy (Picrossirius staining), immunofluorescence and electron microscopy. Subsequently, keratinocytes were cultured on ni- and i-HAMs, and either immersed or positioned at the air-liquid interface. The basement membranes of the ni-HAM group remained intact following de-epithelialization, whereas the i-HAM group displayed no evidence or remnant presence of these membranes. Concerning the keratinocyte cultures, the ni-HAM substrate promoted the growth of multi-layered and differentiated epithelia. Keratinocytes cultured on i-HAM formed epithelium composed of three layers of stratification and discrete cell differentiation. The glycerolated HAM was compatible with cultured epithelia, demonstrating its potential as a skin substitute. Irradiation at 25 kGy caused structural damage to the amnion.